Spatial dimensions of New Zealand's environmental management. (1st August 2013) - McNeill, Jeffrey; Cheyne, Christine; Summers, Rachel
Abstract: New Zealand's regional council boundaries drawn as part of the 1989 local government reforms privilege integrated catchment management. This privilege is now challenged by calls to both fragment and amalgamate councils and centralise decision‐making but with little analytic assessment of the spatial differentiation to support them. The spatial underpinnings of these calls were explored using a case study that assessed the spatial dimensions of environment management. Analysis of the Land Environments and River Environment Classification databases and councils' planning documents highlights challenges local governments face in applying integrated natural resource management within single purpose jurisdictions and implications for wider sustainable development policy.